The Return of Refugees to the Balkans: Between Politics and Everyday Life - Bagić, Dragan (2004)
Almost a decade after the end of war conflicts and last large-scale exodus of people, the return of refugees is still one of the most important political issues in Croatia and Bosnia and Herzegovina as well as in other countries emerging from the break-up of former Yugoslavia. The return of refugees remains one of the key issues that international organizations such as OSCE and EU monitor in this area and with which they condition further integration of these countries into the European Union. On the other hand, due to the long period of displacement, there is a significantly lower likelihood for a large-scale return which makes the politician's interest in this issue absurd. Findings by an empirical research on which this paper is based show that only a small number of Serbian refugees from Croatia and Croatian refugees from Bosnia and Herzegovina are interested in returning to their former homes. Of about 240, 000 Serbian refugees from Croatia currenlty living in Serbia and Montenegro and Bosnia and Herzegovina, only 13% are considering returning to Croatia whereas only 1% are sure to return. The interest in return is even lower among ethnic Croats who fled from Bosnia and Herzegovina and currently live in Croatia. The majority of refugees from both populations have integrated into societies in which they have lived for almost ten years ; they developed a feeling of belonging there, found jobs, built new homes, made new friends and formally regulated their civil status. At the end, the paper examines factors influencing the likelihood for return of refugees who fled war conflicts in former Yugoslavia in the beginning of 1990's and expresses a doubt that the return process, in the given circumstances, could not have yielded better results even if the international community got more engaged and even if the government in the country of the return showed more good will. There is a range of not only political but also social, economic and psychological factors which made a mass return of refugees on the territory of former Yugoslavia a relatively rare occurrence.